Weed Suppression and Tolerance in Winter Oats. (6th September 2017) - Fradgley, Nick S.; Creissen, Henry E.; Pearce, Helen; Howlett, Sally A.; Pearce, Bruce D.; Döring, Thomas F.; Girling, Robbie D.
Abstract : A crops ability to both suppress weed growth and tolerate weed competition is a key consideration when taking an agroecological approach to weed management. Amongst other cereals, oats are widely considered to have superior weed competitiveness yet studies examining competitive ability of oat varieties are rare. We investigated the ability of oats to suppress weeds and yield in the presence of competition from weeds in trials involving five husked and three naked oat varieties at an organic site in the east of England over four trial years (2009-13). We identified a number of key traits that were important for weed suppression including establishment rate, tillering ability, and early leaf area index (LAI) which highlight the importance of rapid early growth rate. Furthermore, taller varieties tended to be more weed tolerant but not necessarily more suppressive. Trade-offs between competitive traits and yield were not found in this study. Crop tillering ability was highlighted as an important trait for selection due to its beneficial effects on weed suppression as well as grain yield and also its high heritability.